Evaluation of Asteraceae herbal extracts in the management of diabetes and obesity. Contribution of caffeoylquinic acids on the inhibition of digestive enzymes activity and formation of advanced glycation end-products (in vitro) - Spínola, Vítor (2021)
The study was performed to assess, for the first time, the in vitro anti-diabetic potential of ten Asteraceae plant extracts to inhibit the activity of digestive enzymes (α-amylase, α-, β-glucosidases and lipase) responsible for hydrolysis/digestion of sugar and lipids. Prevention of advanced glycation end-products (AGEs) formation was evaluated in bovine serum albumin/ribose glycation reaction model. The phytochemical profiles and caffeoylquinic acids (CQAs) contents were determined for the methanolic extract of each plant. Analyzed plant extracts exhibited significant inhibitory activity against key digestive enzymes linked to type II diabetes and obesity. A strong inhibition was observed for glucosidases and mild activity towards amylase and lipase (compared to reference compounds). Moreover, some extracts exhibited potent ability to prevent formation of AGEs, implicated in some diabetic complications. Caffeoylquinic acids were dominant in all plant extracts and findings demonstrate that these compounds are the most relevant hypoglycemic and anti-glycation agents. From the obtained results, Argyranthemum pinnatifidum, Helichrysum melaleucum, and Phagnalon lowei are good candidates for further development of phyto-pharmaceutical preparations as complementary therapy for diabetes and obesity control.